Analysis of the Differences in Flavor Substances and Metabolites from Apple Cider Vinegar Fermented with Different Apple Juices - Dan GAN; Weixian MO; Wei LI (Shipin gongye ke-ji)
In order to develop a fermented apple cider vinegar with excellent flavor. In this study, different apple juices were used as raw materials. Through electronic nose, electronic tongue, GC-MS and non-targeted metabolomics techniques, the effects of characteristic flavor substances, volatile flavor compounds and metabolites of different apple cider vinegar were explored. The results of electronic nose and electronic tongue indicated that the overall odor of apple cider vinegar was composed of nitrogen oxides, methyl compounds, sulfides, alcohols, aldehydes, ketones, ethers and aromatic compounds. The overall flavor of apple cider vinegar fermented from different apple juices was similar, among which PG-3 had the strongest acidity and the most intense odor. The GC-MS results showed that a total of 78 compounds were parsed from the three groups of samples, among which 16 were odor-active compounds, contributing significantly to the flavor of apple cider vinegar. Except for acetic acid, isoamyl acetate had the highest content in all three groups of samples, which was an inherent aroma component of apples. This was followed by isoamyl alcohol, which contributed a floral note to apple cider vinegar. Other key aroma constituents included (E,Z)-2,6-nonadienal, nonanal, phenethyl acetate, phenylethyl alcohol, and benzaldehyde. The non-targeted metabolomics results showed that the KEGG pathways annotated by the three groups of samples accounted for the highest proportion of the metabolism pathways. Biosynthesis of cofactors, nucleotide metabolism, biosynthesis of plant secondary metabolites, flavonoid biosynthesis, purine metabolism, ABC transporters, cutin, suberine and wax biosynthesis were important metabolites transformation pathways during cider vinegar fermentation. Therefore, PG-3 had a more intense and complex aroma in three different types of apple cider vinegar, indicating that apple cider vinegar fermented with organic concentrated apple juice was superior in flavor to ordinary concentrated apple juice and freshly squeezed red Fuji apple juice.